Estudio palinológico en especies de Asplenium (Aspleniaceae) de Argentina - Gamen, María Alejandra (2013)
Palynological study in Asplenium species (Aspleniaceae) from Argentina. The genus Asplenium L. is represented in Argentina by about 38 species, being its habit terrestrial, saxicolous or ephiphytic. In this contribution we complete the palynological study of the genus in this country. The material was processed according to standard techniques for observation under light and scanning electron microscopes. The spores are monolete, the wall formed by the homogeneous exospore, with smooth surface, and the camerate and folded perispore. Two types of folds, winged and ridged, are registered. A variability in the density of the perforations in the outer layer of the perispore, and the margin and sculptural elements of the folds and in the areas between them, are also observed. Spores of analyzed taxa are described and illustrated with pictures using scanning electron microscope.